Komparasi Metode Isolasi DNA Patogen Antraknosa dan Bulai untuk Deteksi PCR - Ade Syahputra; Kikin Hamzah Mutaqin; Tri Asmira Damayanti (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Polymerase chain reaction (PCR) is an important tool for detection, identification and monitoring of quarantine pests in Indonesia. DNA isolation method from target organism is an important step to provide adequate DNA template for performing PCR. Objective of the research was to compare conventional, commercial kit, FTA-card and its modification methods of DNA isolation to be used in PCR detection for Colletotrichum acutatum and Peronosclerospora sorghi from chili and maize, respectively. DNA obtained from various isolation methods were measured using UV-vis nanodrop-spectrophotometry. DNA amplification was performed using DNA concentration of 15 ng µL-1 from each isolation method with gradual primer concentrations of 0.4; 0.6; 0.8; and 1.0 mM. The highest concentration of DNA was achieved with conventional methods for C. acutatum from pure culture and P. sorghi from maize leaf. Best DNA purity was obtained from isolation method using commercial kit for C. acutatum from infected fruit (1.94) and from conventional method for C. acutatum from pure culture (1.91). The highest total yield of isolated DNA was achieved by modified FTA-card for C. acutatum from pure culture. In general DNA amplification using various primer concentration gave positive results although DNA bands intensity was varied from faint to very bright. Furthermore PCR optimization using the best primer concentration from previous reaction showed that all DNA templates resulted in thick and bright DNA bands.